Uso de gesso e residuos de leguminosas para melhorar a enraizabilidade de um solo tropical coeso e aumentar a produtividade do milho. - Portela, Stefanny Barros (2016)
In this way, the interactions between high atmospheric evaporation, low availability of nutrients and reduction in the thickness of the rootable layer, they can reduce crop growth and make agrosystems unviable. Therefore, increasing the volume of soil explored by crop roots is crucial to efficiency of water and nutrient use in the viability of crop systems in the humid tropic region. Therefore, this work aims to evaluate the combination of effects of gypsum with tree legume biomass on calcium levels and soil organic carbon in the root zone and how this may affect resistance to soil penetration, nitrogen absorption and corn yield in a soil sandy prone to cohesion